![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
3个回答
展开全部
先令x^6+3=t
f(x)=(t^7+x)^7
令t^7+x=u
f(x)=u^7
f'(x)=7u^6u'
u'=7t^6t'+1
t'=6x^5
则
f'(x)=7[(x^6+3)^7+x]^6×[7(x^6+3)^6×6x^5+1]
f(x)=(t^7+x)^7
令t^7+x=u
f(x)=u^7
f'(x)=7u^6u'
u'=7t^6t'+1
t'=6x^5
则
f'(x)=7[(x^6+3)^7+x]^6×[7(x^6+3)^6×6x^5+1]
展开全部
f(x)=[(x^6 + 3)^7 + x]^7
f'(x)=7[(x^6 + 3)^7 + x]^6*7*(x^6+3)^6*6x^5
=294x^5(x^6+3)^6*[(x^6 + 3)^7 + x]^6
f'(x)=7[(x^6 + 3)^7 + x]^6*7*(x^6+3)^6*6x^5
=294x^5(x^6+3)^6*[(x^6 + 3)^7 + x]^6
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
f'(x)=7[(x^6+3)^7+x]^6*[7(x^6 + 3)^6+1]*6x^5
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询